Antitumor activity of lurbinectedin in second-line small cell lung cancer patients who are candidates for re-challenge with the first-line treatment. (December 2020) - Subbiah, Vivek; Paz-Ares, Luis; Besse, Benjamin; Moreno, Victor; Peters, Solange; Sala, María Angeles; López-Vilariño, José Antonio; Fernández, Cristian; Kahatt, Carmen; Alfaro, Vicente; Siguero, Mariano; Zeaiter, Ali; et al.
Highlights: The NCCN recommends first-line re-challenge for relapsed SCLC with CTFI ≥ 180 days. This recommendation is based on data from small trials from the 1980s. Lurbinectedin has remarkable activity and acceptable safety in second-line SCLC. ORR was 60.0 % in a preplanned subset of patients with CTFI ≥ 180 days. Lurbinectedin can be a valuable alternative to re-treatment with first-line therapy. Abstract: Introduction: The National Comprehensive Cancer Network guidelines recommend re-challenge with the first-line treatment for relapsed small cell lung cancer (SCLC) with chemotherapy-free interval (CTFI)≥180 days. A phase II study (NCT02454972) showed remarkable antitumor activity in SCLC patients treated with lurbinectedin 3.2 mg/m 2 1 -h intravenous infusion every 3 weeks as second-line therapy. We report results for the pre-planned subset of patients with CTFI ≥ 180 days. Material and Methods: Twenty patients aged ≥18 years with pathologically proven SCLC diagnosis, pretreated with only one prior platinum-containing line, no CNS metastases, and with CTFI ≥ 180 days were evaluated. The primary efficacy endpoint was the overall response rate (ORR) assessed by the Investigators according to RECIST v1.1. Results: ORR was 60.0 % (95 %CI, 36.1−86.9), with a median duration of response of 5.5 months (95 %CI, 2.9−11.2) and disease control rate of 95.0 % (95 %CI, 75.1−99.9). Median progression-free survival was 4.6 months (95 %CI, 2.6−7.3). With a censoring of 55.0 %, the median overall survival was 16.2 months (95 %CI, 9.6-upper level not reached). Of note, 60.9 % and 27.1 % of patients were alive at 1 and 2 years, respectively. The most common grade 3/4 adverse events and laboratory abnormalities were hematological disorders (neutropenia, 55.0 %; anemia; 10.0 % thrombocytopenia, 10.0 %), fatigue (10.0 %) and increased liver function tests (GGT, 10 %; ALT and AP, 5.0 % each). No febrile neutropenia was reported. Conclusion: Lurbinectedin is an effective treatment for platinum-sensitive relapsed SCLC, especially in patients with CTFI ≥ 180 days, with acceptable safety and tolerability. These encouraging results suggest that lurbinectedin can be another valuable therapeutic option rather than platinum re-challenge.